The Physics and the Chemistry of Michael Faraday to form for citizenship - Nogueira, S. R.A.; Cardoso, F. S.; Carvalho, F. L.C. [UNESP]; Marinelli, M. O.; Bezerra, A. S.; Senra, P. R. (IOP Publishing, 2019)
In this paper we present a teaching-learning strategy based on the life of Faraday to provide knowledge of physics (electromagnetic induction) and chemistry (chemical bonds) and a wakening to citizenship. The strategy combined a film screening with experimentation and was applied with 4 classes of the first-grade secondary school in 2014 and 2016. In all classes the discussions about the movie and the student's reports showed that they appropriated the specifics concepts, they got enchanted by Faraday's life and became aware of their own capacity to build their future.